Optimization of lipase-mediated synthesis of 1-nonene oxide using phenylacetic acid and hydrogen peroxide - Abdul Malek, Emilia; Arumugam, Mahashanon; Basri, Mahiran; Abdul Rahman, Mohd Basyaruddin (MDPI AG, 2012)
Herein, an efficient epoxidation of 1-nonene is described. In a simple epoxidation system, commercially available Novozym 435, an immobilized Candida antarctica lipase B, and hydrogen peroxide (H2O2) were utilized to facilitate the in situ oxidation of phenylacetic acid to the corresponding peroxy acid which then reacted with 1-nonene to give 1-nonene oxide with high yield and selectivity. The aliphatic terminal alkene was epoxidised efficiently in chloroform to give an excellent yield (97%–99%) under the optimum reaction conditions, including temperature (35 °C), initial H2O2 concentration (30%), H2O2 amount (4.4 mmol), H2O2 addition rate (one step), acid amount (8.8 mmol), and stirring speed (250 rpm). Interestingly, the enzyme was stable under the single-step addition of H2O2 with a catalytic activity of 190.0 Ug−1. The entire epoxidation process was carried out within 12 h using a conventional water bath shaker.